Treatment of small intestinal bacterial overgrowth: Conventional antibiotic therapy and alternative therapy - probiotics and low FODMAP diet - Litwiniuk, Maria; Zaniuk, Marcin; Hurkała, Kamil; Antonik, Dominika; Denys, Barbara; Góra, Karolina; Zdziennicki, Wojciech; Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the study: Small intestinal bacterial overgrowth syndrome (SIBO) is a syndrome characterized by an increased number of bacteria in the small intestine. The condition causes many non-specific symptoms such as diarrhea, abdominal pain and bloating. The purpose of this study is to review the current knowledge regarding treatment options for SIBO. Methodology: A literature review was conducted based on PubMed, GoogleScholar databases and American College of Gastroenterology (ACG) guidelines. Current knowledge: SIBO is a heterogeneous syndrome. Symptoms of bacterial overgrowth include bloating, abdominal pain and abnormal bowel motility. In more severe cases, patients may experience malabsorption leading to weight loss and malnutrition. SIBO can occur in healthy individuals, but very often accompanies other conditions. The primary test for diagnosis is non-invasive lactulose or glucose breath tests. For treatment, the antibiotic rifaximin is preferred. It exhibits a broad spectrum of activity and a low toxicity profile. Treatment may also include diet therapy and the use of probiotics. Summary: SIBO continues to be both a diagnostic and therapeutic problem. Effective treatment includes not only elimination of the bacteria but also treatment of predisposing conditions. Conclusions of the study show a positive effect of rifaximin on the reduction of SIBO symptoms and improvement of patients' quality of life. The use of certain probiotics has a proven effect. According to the currently available literature, the effectiveness of the low-FODMAP diet in SIBO is hypothetical and further studies are needed to unequivocally confirm its efficacy.